Changes to intraocular pressure and its correlation with corneal diameter in infants aged from 0 to 36 months - Wang, Jian-Cang; Du, Fei-Fan; Meng, Shuo-Shuo; Wei, Yun-Shuo; Guo, Xi-Ting (Frontiers in Pediatrics, 2022)
Objective: This study examines the distribution and development of intraocular pressure (IOP) in infants aged from 0 to 36 months and analyzes its correlation with corneal diameter. Methods: The study used a retrospective case analysis methodology. Healthy infants treated in the ophthalmology department of Hebei Children’s Hospital from December 2012 to December 2020 were included in the study. Among these infants, 385 had their IOP measured, and 432 had their corneal diameters measured. Furthermore, information such as birth history, growth and development, IOP, and corneal diameter were collected. Their IOPs were measured with an iCare portable rebound tonometer when the child was awake and calm, and the corneal diameter was measured with a Castroviejo caliper under chloral hydrate sedation. The infants were divided into five groups according to age, and SPSS statistical software was used to analyze, compare, and correlate IOP and corneal diameter variations. Results: The mean IOP values of 0–1 month, 1–6 months, 6–12 months, 12–24 months and 24–36 months groups were 7.42 ± 1.92, 9.10 ± 2.85, 12.00 ± 3.15, 13.72 ± 3.09, and 15.14 ± 2.67 mmHg, respectively. The differences in IOP of the 0–1 month old infants and the 1–6 months old infants with the other three groups were statistically significant; the difference in IOP between the 6–12 months group and the 24–36 months group was statistically significant. In the studied groups, the horizontal corneal diameters were 9.78 ± 0.14, 10.50 ± 0.29, 10.86 ± 0.23, 11.38 ± 0.07, and 11.72 ± 0.04 mm, respectively, and the vertical diameters of the cornea were 9.28 ± 0.26, 10.07 ± 0.18, 10.28 ± 0.14, 10.56 ± 0.24, and 10.85 ± 0.03 mm, respectively. The differences in the vertical and horizontal diameters of the cornea among the groups were statistically significant. Conclusion: Infants’ IOP and corneal diameter positively correlate with age, and they peak in the first 12 months.